Integrating Islamic-Based Edu-Tourism and Creative Economy for Sustainable Village Development in Kampung Inggris Pare, Indonesia - Asharsyira, Almeyda (Unisia, 2025)
This study examines the integration of educational tourism (edu-tourism) and the creative economy in Kampung Inggris Pare, East Java, an educational village known for its non-formal English language learning ecosystem. The research aims to design a sustainable village development model based on Islamic economic values, emphasizing participation, justice, and general welfare. Using an exploratory descriptive qualitative approach, the study employs field observations, in-depth interviews, and a literature review to analyze the socio-economic dynamics shaping the community. The findings reveal a paradox: while Kampung Inggris Pare thrives as an educational hub, local community involvement in the tourism economy remains limited. Despite the growth of hundreds of language institutions attracting thousands of students monthly, most institutions operate independently, reducing local participation and limiting the economic multiplier effect. The study suggests that integrating the pentahelix collaboration framework and maqāṣid al-sharī‘ah principles can create an inclusive governance model for the development of Islamic edu-tourism. The proposed model connects language institutions, local businesses, village governments, academia, and media in a collaborative effort. The study contributes to the field by offering an Islamic Edu-Creative Tourism Governance Model, balancing economic growth, social justice, and moral integrity. These findings provide insights for future research and policy formulation, suggesting further exploration through mixed-methods approaches and comparative studies to deepen understanding and enhance the sustainability of community-based tourism in alignment with Islamic values.